Senior High School Students’ Perceptions of the Practicality of the Materials in the English Workbooks Used in Their EFL Class - Rizqi Budi Nurani; Siti Masrifatul Fitriyah; Annur Rofiq (EFL Education Journal, 2023)
This research titled “Senior High School Students’ Perceptions of the Practicality of the Materials in the English Workbooks Used in Their EFL Class” aims to raise the awareness regarding to the importance of the aspect of practicality in senior high school students’ workbooks. This study was based on finding out whether or not the material contained in the senior high school students’ workbooks are practical to be used or applied in their daily life situations based on their perspectives, hence this is qualitative research. The participants of this study were two senior high school students that are currently studying in their twelfth grade in one of the senior high schools in Jember. The data was collected by an individual recorded-interview, which then transcribed into a written form and analyzed using Braun and Clarke’s Thematic Analysis Method (2008). The materials that were talked about contained in the participants’ workbook. The findings of this study revealed that most of the materials contained in the participants’ workbook are practical, which implied that those materials are proven to be helpful for students to be applied in their daily-life situations.